APLIKASI PENJADWALAN PERAWATAN MESIN PADA LABORATORIUM PERMESINAN DASAR DI BENGKEL MEKANIK POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Selvi Diana; Linda Fujiyanti; Yang Agita Rindri (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The development of technology is currently used in various fields of science to make work easier. Because of the many features available, it is hoped that this application can be used to display machine maintenance schedules up to complexcity value of 30. By using this application, you can computerize the entire planning calculation process and avoid mistakes in making maintenance plans and damage due to forgetting to do routine maintenance. The application you are building uses the PHP programming language to help developers develop additional applications. It also uses the Codeigniter framework to make the programming process easier for developers. Supported by the waterfall method. This application can also monitor machine maintenance in the basic machinery laboratory of the Bangka Belitung State Manufacturing Polytechnic mechanic workshop